Tipologi Financial Technology Paylater: Technology Acceptance Model (TAM) - Herlina; Destriana Widyaningrum; Giovanny Theotista (PT FORMOSA CENDEKIA GLOBAL, 2023)
The use of paylater fintech is currently mushrooming among the public because it makes it easier for people to shop online. The typology of fintech paylaters is based on the Technology Acceptance Model (TAM) method to determine the contribution of the magnitude of the Technology Acceptance Model (TAM) aspect in explaining the use of fintech paylaters. The study used a sample of 101 fintech paylater respondents who live in Jakarta and data analysis techniques used Tructural Equation Modeling (SEM-AMOS) with the First Order Confirmatory Factor Analysis (CFA) technique. The results showed that the contribution of the Technology Acceptance Model (TAM) aspects in explaining the use of the Technology Acceptance Model (TAM) was the Technology Acceptance Model (TAM) respectively, namely Perceived Usefulness of 93.7%, Attitude Toward Using of 93.7 %, Perceived Ease of Use of 92.20%, Behavioral Intention to Use of 78.5% and lastly Actual Use of 43.9%.